2009
DOI: 10.1038/labinvest.2008.109
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet overproduction of H2S and suppressed insulin release in Zucker diabetic rats

Abstract: Hydrogen sulfide (H 2 S) has been traditionally known for its toxic effects on living organisms. The role of H 2 S in the homeostatic regulation of pancreatic insulin metabolism has been unclear. The present study is aimed at elucidating the effect of endogenously produced H 2 S on pancreatic insulin release and its role in diabetes development. Diabetes development in Zucker diabetic fatty (ZDF) rats was evaluated in comparison with Zucker fatty (ZF) and Zucker lean (ZL) rats. Pancreatic H 2 S production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(168 citation statements)
references
References 43 publications
5
156
2
3
Order By: Relevance
“…Additionally, Kaneko et al suggested that elevation of the H 2 S levels as a result of L-cysteine metabolism may inhibit insulin release from isolated mouse islets and the mouse ␤-cell line MIN6 under diabetic conditions (11). In ZDF rats, abnormally high pancreatic production of H 2 S has been reported to suppress insulin release (101). These findings indicate that high concentrations of H 2 S in pancreas could have deleterious effects on the development of diabetes and that new therapeutic measures for diabetes may involve inhibiting endogenous H 2 S production from pancreas.…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Diseases?mentioning
confidence: 99%
“…Additionally, Kaneko et al suggested that elevation of the H 2 S levels as a result of L-cysteine metabolism may inhibit insulin release from isolated mouse islets and the mouse ␤-cell line MIN6 under diabetic conditions (11). In ZDF rats, abnormally high pancreatic production of H 2 S has been reported to suppress insulin release (101). These findings indicate that high concentrations of H 2 S in pancreas could have deleterious effects on the development of diabetes and that new therapeutic measures for diabetes may involve inhibiting endogenous H 2 S production from pancreas.…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Diseases?mentioning
confidence: 99%
“…Increases in CBS and CSE expression and H 2 S production in these diabetic tissues are reversed by insulin treatment, suggesting that this may be a secondary result from hyperglycemia or hypoinsulinemia. In Zucker diabetic fatty (ZDF) rats, which are a diabetic model with obesity and hyperinsulinemia, CSE expression is elevated in the islets (22). Intraperitoneal administration of PPG, but not of aminooxyacetate, a putative selective inhibitor of CBS, improves glycemic control in vivo in ZDF rats (22).…”
Section: H 2 S and Diabetes Mellitusmentioning
confidence: 99%
“…In Zucker diabetic fatty (ZDF) rats, which are a diabetic model with obesity and hyperinsulinemia, CSE expression is elevated in the islets (22). Intraperitoneal administration of PPG, but not of aminooxyacetate, a putative selective inhibitor of CBS, improves glycemic control in vivo in ZDF rats (22). However, non-obesediabetic (NOD) mice, another model of type 1 diabetes that results from an autoimmune disorder, show a progressive reduction of plasma H 2 S levels (29).…”
Section: H 2 S and Diabetes Mellitusmentioning
confidence: 99%
“…H 2 S is produced in various types of cells via the enzymatic function of two enzymes: cystathionine β-synthase (CBS) and cystathionine γ-lyase (CSE) [1]. CSE has been shown to be the predominant H 2 S-generating enzyme in pancreatic beta cells [2] and freshly isolated rat islets [3].…”
Section: Introductionmentioning
confidence: 99%